Dialectics Of Islam With Javanese And Sunda Wiwitan Culture (Phenomenological Study In The Jalawastu Traditional Community In Brebes Regency And Bonokeling In Banyumas Regency) - Dimas Indianto S.; Nur Rohmah Hayari; Ahsan Hasbullah; Alhairi Alhairi; Ana Dwi Wahyuni (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2024)
This study examines the dialectic between Islam and Kejawen and Sunda Wiwitan culture, which is reflected in the lives of the Jalawastu indigenous people in Brebes and Bonokeling in Banyumas. Using a phenomenological approach, this study seeks to understand how the interaction and integration of Islamic values with local traditions shape the cultural identity of the community. This study uses a phenomenological approach. The results of the study indicate that this dialectic process involves adaptation, acculturation, and negotiation of values that occur dynamically. In the context of Jalawastu and Bonokeling, Kejawen and Sunda Wiwitan cultures are not completely replaced by Islamic teachings, but instead form a complementary harmony. Traditional rituals, religious symbols, and social structures of society become the main spaces where Islam and local cultures interact with each other. This study emphasizes the importance of respecting cultural diversity in Islam and the role of religion as a medium of reconciliation that strengthens social cohesion in indigenous communities. This study also contributes to cross-cultural and religious understanding, which is relevant in the context of Indonesia as a multicultural country.Keywords: Islam, Kejawen, Sundanese Wiwitan, Jalawastu, Bonokeling, dialectics, phenomenology.